Hubungan Karakteristik Kelompok Wanita Tani dan Efisiensi Produksi Usahatani Jamur Berbasis Data Envelopment Analysis - Palinja, Bintang Akbar; Euriga, Epsi; Rimartin, Geraldo Adinugra (AGRITEXTS: Journal of Agricultural Extension, 2026)
Oyster mushroom cultivation by Women Farmers Groups (KWT) in Condongcatur Village has great potential in supporting urban food security, but still faces production efficiency issues. This study aims to analyze the efficiency scores of mushroom farming and their relationship with KWT characteristics, including: age, education, leadership, business facilities, and use of the Internet of Things (IoT). The research method used Data Envelopment Analysis (DEA) with an output-oriented Variable Returns to Scale (VRS) model on 12 KWTs, accompanied by descriptive and correlation analysis with 35 respondents. The results showed that six KWTs had achieved optimal efficiency scores, while the other six KWTs were still inefficient. The correlation analysis showed that leadership and business facilities had a positive and significant (moderate) relationship, while the use of IoT had a positive and significant (strong) relationship to the efficiency score of oyster mushroom farming. This study provides recommendations for the need for extension regarding the use of IoT in KWTs that have not implemented it by looking at KWTs that have implemented it.